2018
DOI: 10.15761/cmid.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of febrile patients reveals unnoticed epidemic of zika fever in Dielmo, Senegal, 2000

Abstract: Background: In Africa, recent malaria controls unveiled a large proportion of febrile illnesses of unknown origin. Few studies have been undertaken to identify these pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…IgM antibodies to DENV-2 were detected in November 1988 and November 1991 in 4.6–5.7% and 0.8% of individuals examined, respectively. Authors in [ 40 ] reported a high prevalence of the Zika virus antibody during a seroprevalence study in the Dielmo area (located in the Fatick region where a DENV outbreak occurred in 2018). All these previous studies, combined with the frequent molecular detection of other dengue serotypes in Senegal [ 19 , 41 , 42 ], have stressed that there is a risk of more severe dengue outbreaks in the future, manifesting antibody-dependent enhancement (ADE) as is the case for regions with serotype co-circulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgM antibodies to DENV-2 were detected in November 1988 and November 1991 in 4.6–5.7% and 0.8% of individuals examined, respectively. Authors in [ 40 ] reported a high prevalence of the Zika virus antibody during a seroprevalence study in the Dielmo area (located in the Fatick region where a DENV outbreak occurred in 2018). All these previous studies, combined with the frequent molecular detection of other dengue serotypes in Senegal [ 19 , 41 , 42 ], have stressed that there is a risk of more severe dengue outbreaks in the future, manifesting antibody-dependent enhancement (ADE) as is the case for regions with serotype co-circulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to YFV, which has a long history of human infection in Africa [ 42 , 90 ], the African genotype ZIKV currently appears to be maintained through a sylvatic cycle, and human infections still appear to be rare. However, our own serological data from active surveillance of arboviruses in Senegal indicate that asymptomatic ZIKV infections may be more widespread than assumed [ 91 ]. If confirmed, asymptomatic or unnoticed infection could be an alternative explanation for the higher CAI values for the human genome of the African genotype ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of DENV, YFV, RVFV, CHIKV, and ZIKV IgM in samples was assessed by a capture ELISA (MAC ELISA), following a published protocol. 15 RNA extracts from nasopharyngeal swabs were subjected to detection of respiratory viruses using a two-step real-time multiplex RT-PCR using Anyplex RV16 (Seegene) following the published protocol 16 performed on the Bio-Rad CFX-96 thermocycler (Bio-Rad Laboratories). In brief, we used multiplex PCR targeting 16 respiratory virus distributed across two panels (A and B): Adenoviruses, Influenza (A and B), Parainfluenza virus (1, 2, 3, and 4), and Rhinoviruses (A, B, and C) on panel A; and Respiratory syncytial viruses (A and B), Bocavirus, Metapneumovirus, Enterovirus, and Coronavirus (229E, NL63, and OC43) on panel B.…”
Section: Methodsmentioning
confidence: 99%